Strategi K-Radio Jember dalam Upaya Pemanfaatan Media Sosial sebagai Upaya Mempertahankan Audience di Era Digital - Rohim, Amatullah Azka Faadiya Haya Nurilalamin (Icon: Islamic Communication and Contemporary Media Studies, 2024)
In the midst of many radio stations losing listeners due to switching to digital media, K Radio Jember is here which can stand up to adapt to the era. By combining mass media with digital media, K Radio Jember is growing rapidly, and is even able to increase its audience. Through his social media accounts, it is proven that his followers and audience con-tinue to increase. So this is an interesting thing to research.The objec-tives of this thesis research are: 1) To determine K Radio Jember's strat-egy in utilizing social media as an effort to maintain its audience in the digital era. 2) To find out how K Radio Jemberis converging in facing the digital era.This research uses a qualitative approach method with a de-scriptive type. This research used observation, interviews and documen-tation to collect data. Data analysis techniques use data condensation, data presentation and data verification or conclusions. And for data va-lidity techniques in this research, triangulation analysis of data sources and techniques is used.This research concluded that: 1) K Radio's strat-egy in using social media as an effort to maintain its audience in the Dig-ital Era is the Compatibility Strategy, K Radio adapts to market seg-ments. Habit Formation Strategy, K Radio has a variety of regular week-ly program schedules. Control of Audience Flow Strategy. K Radio carries out monthly evaluationsand creates interesting content. Mass Appeal Strategy. K Radio has forayed into digital media through live streaming, and K Radio has become a space for aspirations and a way of connecting with the community. 2) The influence of K Radio in the use of social me-dia to maintain the audience, namely the audience is increasing and trusting K Radio, income, and becoming a forum for community aspirations and liaison.